Exploring Nature in English: Belajar Kosakata Bahasa Inggris Dasar tentang Alam - Mahmud, Muzdalifah (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Vocabulary acquisition is one of the fundamental aspects of English language learning, especially for primary school-aged children who are in the early stages of language acquisition. Basic vocabulary related to nature was chosen because it has proximity to the child’s daily life, making it more understandable and interesting to learn. This community service activity was implemented by Gorontalo State University English Education lecturers with the aim of introducing basic English vocabulary on nature to primary school children of grades 4-6 in Tilongkabila Subdistrict, Bone Bolango County, Gorontalo Province. The activity implementation method uses a nature-based exploration approach through outdoor learning in the courtyard. Activities take place in one encounter with stages in the form of ice breaking, vocabulary introduction using pictured cards and real objects, as well as simple game activities to reinforce comprehension. Evaluation was conducted qualitatively through observation of children’s responses during the activity, including enthusiasm, engagement, and ability to pronounce the taught vocabulary. Activity results showed that the children were very enthusiastic, active, and capable of naming a number of basic nature-related vocabulary although with pronunciation that still needed guidance. These activities provide a fun learning experience, increase motivation, and foster children’s interest in continuing to learn English through a contextualized nature-based approach.